SIMULASI PROSES PRODUKSI KERUPUK KULIT DOROKDOK PD.ABC SUKAREGANG – GARUT - Muchtar, Diki; Herdiansyah, Ferry; gumelar, indra (Jurnal Teknologika, 2024)
PD.ABC experienced problems with an inefficient production system. This is indicated by the minimum amount of output that can be sent. This becomes a source of problems when there is a large order of dorokdok skin crackers, which cannot be completely filled. Therefore, this research will analyze the factors that become obstacles in the dorokdok skin cracker production system using a system modeling and simulation approach. The conclusion was that in the PD dorokdok skin cracker production system. ABC still lacks workers for the production process. This causes the failure rate in sending dorokdok skin crackers to still exist and losses occur. With 2 operators, the maximum output produced is only 63 pcs/day with costs incurred of Rp. 2,950,000 and the profit obtained is only Rp. 1,260,000 or it could be interpreted that PD.ABC suffered a loss of Rp. 1,690,000. After improvements were made, by adding 3 operators it was seen that the simulation results did not show any failures in the production process flow of dorokdok skin crackers with the maximum output produced being 500 pcs/day, the total costs incurred amounting to IDR 6,850,000 and the profit obtained amounting to IDR 10,000,000 or it could be interpreted as PD.ABC experiencing a profit of IDR 3,150,000. So it can be concluded that the improvements made have been effective by increasing human power thereby increasing PD dorokdok skin cracker production capacity. A B C